Intraoperative application of low-dose dexmedetomidine or lidocaine for postoperative analgesia in pediatric patients following craniotomy: a randomized double-blind placebo-controlled trial - Bao, Di; Wang, Yaxin; Xiong, Wei; Zhang, Di; Qiao, Lanxin; Zheng, Na; Li, Lu; Jin, Xu (Frontiers in Surgery, 2024)
Background Postoperative pain is a common occurrence in pediatric patients following craniotomy, often leading to negative outcomes. Intravenous dexmedetomidine and lidocaine are commonly used adjuvant medicines in general anesthesia to reduce perioperative opioid consumption and relieve postoperative pain in adults. While they show promise for use in pediatrics, the evidence of their application in pediatric craniotomy patients is limited. Therefore, we aimed to compare the effects of dexmedetomidine and lidocaine on postoperative pain in pediatric patients following craniotomy. Methods We conducted a randomized, double-blind, single-center trial on children scheduled for craniotomy. The 255 recruited participants aged 1–12 years were randomly assigned to intraoperatively receive a loading intravenous dose of either dexmedetomidine 1 μg·kg−1 or lidocaine 2 mg·kg−1 or normal saline for 15 min followed by dexmedetomidine 0.5 μg·kg−1·h−1 or lidocaine 1 mg·kg−1·h−1 or normal saline until the sutures of endocranium were completed. The primary outcome was the cumulative sufentanil consumption within 24 h post-surgery. Results A total of 241 patients were included in the statistical analysis. The primary outcome did not show any significant differences among the three groups (median (IQR) lidocaine group: 3.36 (1.32–5.64) μg vs. dexmedetomidine group: 3.12 (1.36–6.39) μg vs. control group 3.46 (1.77–7.62) μg, p = 0.485). Among the secondary outcomes, there was a statistically significant but small reduction in sufentanil consumption within 2 h, postoperative FLACC/WBFS/NRS pain scores within 4 h after surgery and postoperative Ramsay sedation scores in dexmedetomidine group (p < 0.05). Regarding postoperative complications, the incidence of electrolyte disturbance within 24 and 48 h after surgery was significantly higher in control group compared to the other two groups. There were no significant differences in intraoperative opioid consumption, postoperative frequency of remedy medication, or length of hospitalization among the three groups. No adverse events related to lidocaine or dexmedetomidine were observed. Conclusions There were no significant differences in the primary outcome among the three groups. Although dexmedetomidine showed some benefits in reducing postoperative opioid consumption within the first 2 h and pain intensity within the first 4 h post-surgery, these findings should be interpreted with caution. Further research is required to comprehensively assess the outcomes and determine the optimal administration strategy. Clinical Trial Registration [http://www.chictr.org.cn/index.aspx], identifier [ChiCTR1800019411].